Evolution of burn injury management in KATH, Kumasi-Ghana, 1954-2017 - Pius Agbenorku (Elsevier, 2018)
Introduction: Burns management worldwide has evolved over the decades with remarkable improvement, especially in High Income Countries. Knowledge about the various eras; challenges encountered, strategies to overcome them and other vital information are very necessary for underdeveloped and developing countries who hope to attain the best level of burns management. Aim: This paper presents a report on the evolution of burn injury management at the Komfo Anokye Teaching Hospital (KATH)-Ghana, since the hospital's commissioning in 1954 till present (63 years). Method: The evolution of burns management at KATH was categorized into 5 phases: Phase 1, 2, 3, 4 and 5. Each phase provides information on the extent of development spanning from the "all-in-one" inclusive ward through to the new Burns Intensive Care Unit (BICU) at the new Accident and Emergency Centre. Results: There has been significant reduction in burns mortality and other negative burns sequelae. There has also been effective records keeping which has led to effective research work and improved burns care. There is a new BICU, an improvement from the old Burns Ward D2C and is stocked with ultra-modern equipment for burns management. Conclusion: Evolution of the KATH Burns Unit has led to great improvement in burn patient's care. The experience gained so far has better equipped us to mentor upcoming burn centers and healthcare providers across the globe; most importantly in Africa. The goal to put up special burn centers is challenging, but perseverance brings success, and the results are invaluable. Keywords: Burns management, Burns, KATH, BICU, Occupational Therapy